Structure of transcribing RNA polymerase II-nucleosome complex - Lucas Farnung (Nature Portfolio, 2018)
Eukaryotic transcription requires passage of RNA polymerase II (Pol II) through chromatin, which is impaired by nucleosomes. Here the authors report the cryo-EM structure of transcribing Pol II engaged with a downstream nucleosome core particle at an overall resolution of 4.4 Å, providing insights into the mechanism of chromatin transcription.